2020
DOI: 10.3390/ijerph17197228
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being without a Roof: Examining Well-Being among Unhoused Individuals Using Mixed Methods and Propensity Score Matching

Abstract: The morbidity and mortality experiences of people who are unhoused have been well-described, but much less is known about the overall well-being of these individuals. In this mixed methods study, housed and unhoused participants completed a multi-faceted 10 domain measure of well-being (the Stanford WELL Survey), and a subset of unhoused participants shared their experiences during qualitative interviews. Using propensity score matching, unhoused participants (n = 51) were matched at a ratio of 1:5 with housed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…Panadero and coworkers [15] also described an association of happiness with religious belief in HPs, as in other populations [32,35], and HPs were found to score significantly higher for religious and spiritual beliefs in comparison to people with homes [7]. This aspect was not evaluated in our quantitative study and was not raised as a major theme in the interviews with HPs.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Panadero and coworkers [15] also described an association of happiness with religious belief in HPs, as in other populations [32,35], and HPs were found to score significantly higher for religious and spiritual beliefs in comparison to people with homes [7]. This aspect was not evaluated in our quantitative study and was not raised as a major theme in the interviews with HPs.…”
Section: Discussionmentioning
confidence: 48%
“…Little research has been conducted on more subjective aspects such as the general happiness or wellbeing of HPs, which may be useful to support the design of more effective interventions [6]. Ahuja et al [7] found that their subjective well-being was inferior to that of people with homes. The health conditions of HPs pose a major care challenge to nurses working in the community, and an approach that accounts for HPs' own perception of wellbeing and happiness may improve the effectiveness of interventions in this population, such as those that focus on happiness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This echoes the findings of Ahuja et al, who conclude that levels of subjective wellbeing are lower among homeless people (“unhoused people”) compared to housed participants, especially in dimensions such as social connectedness, negative emotions, perceived stressors, and resilience. On the other hand, spirituality and religiosity are more developed among unhoused people, who experience a more pronounced need to search for meaning and connect with a higher being [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Well-being was assessed using the Stanford WELL scale, a 53-item self-report questionnaire assessing nine well-being domains including experience of emotions (both positive and negative), social connectedness, sense of self, spirituality/religiosity, purpose and meaning, stress and resilience, physical health, financial stability, and exploration/creativity ( Chrisinger et al, 2019 , Ahuja et al, 2020 ). Each domain is scored from 0 to 10, with higher scores indicating optimal outcome (e.g., higher well-being, less stress or negative emotions).…”
Section: Methodsmentioning
confidence: 99%